Discrimination of RNA fiber structures using solid-state nanopores. Issue 18 (20th April 2022) - Tripathi, Prabhat; Chandler, Morgan; Maffeo, Christopher Michael; Fallahi, Ali; Makhamreh, Amr; Halman, Justin; Aksimentiev, Aleksei; Afonin, Kirill A.; Wanunu, Meni
Abstract : Nanopore translocation can discriminate the RNA fibers differing from one another in the frequency of the branches. Abstract : RNA fibers are a class of biomaterials that can be assembled using HIV-like kissing loop interactions. Because of the programmability of molecular design and low immunorecognition, these structures present an interesting opportunity to solve problems in nanobiotechnology and synthetic biology. However, the experimental tools to fully characterize and discriminate among different fiber structures in solution are limited. Herein, we utilize solid-state nanopore experiments and Brownian dynamics simulations to characterize and distinguish several RNA fiber structures that differ in their degrees of branching. We found that, regardless of the electrolyte type and concentration, fiber structures that have more branches produce longer and deeper ionic current blockades in comparison to the unbranched fibers. Experiments carried out at temperatures ranging from 20–60 °C revealed almost identical distributions of current blockade amplitudes, suggesting that the kissing loop interactions in fibers are resistant to heating within this range.